1999
DOI: 10.1677/joe.0.1600067
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1alpha regulates G1 cell cycle progression and arrest in thyroid carcinoma cell lines NIM1 and NPA

Abstract: This study provides the first report that the same cytokine (interleukin-1 (IL-1)) can induce opposite effects on cyclin-dependent kinases (Cdks) and Cdk inhibitors (Cdkis) in the G 1 phase even in the same type of cancer cells (papillary thyroid carcinoma cells). Cell cycle analysis revealed an increase in NIM1 cells and a decrease in NPA cells in the S and G 2 +M phases after treatment with IL-1 . The addition of IL-1 to NIM1 cells reduced the expression of p16 and p21 protein and induced the expression of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Tumor cells express many cytokines including IL-1␣, although the number of studies regarding their contribution to the tumor growth and metastasis is still very low. 15 IL-1␣ plays various roles in local inflammation, immunologic reactions, and cell differentiation. 16,17 Regarding gastric carcinoma, Ito et al reported that six of eight cell lines expressed IL-1␣ mRNA at various levels and also confirmed that two of these cell lines secreted IL-1␣ protein into the culture fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells express many cytokines including IL-1␣, although the number of studies regarding their contribution to the tumor growth and metastasis is still very low. 15 IL-1␣ plays various roles in local inflammation, immunologic reactions, and cell differentiation. 16,17 Regarding gastric carcinoma, Ito et al reported that six of eight cell lines expressed IL-1␣ mRNA at various levels and also confirmed that two of these cell lines secreted IL-1␣ protein into the culture fluid.…”
Section: Discussionmentioning
confidence: 99%
“…62 The reason for these changes in the cell cycle remains unclear, though the authors propose that elevated inflammatory cytokines such as IL-1, IL-6, IL-8, and IL-10 in peritoneal fluid of women with endometriosis [63][64][65] can activate several cyclindependent kinase inhibitors in various cells. [66][67][68] However, the precise mechanisms and the reason why cytokines may adversely affect the cell cycle in granulosa cells and consequently have pathologic effects on folliculogenesis remain unexplained. Minguez et al 53 suggested a defect at the level of oocyte activation as a possible mechanism for the implantation failure associated with endometriosis in couples treated with ICSI.…”
Section: Effect Of Inflammatory Mediators Of Endometriosis On Oocyte mentioning
confidence: 99%
“…It has also been reported that these cytokines can activate several cyclin-dependent kinase inhibitors in various cells [20][21][22]. However, the precise mechanisms involved, and the reason for why cytokines adversely affect the cell cycle in the granulosa cells of patients with endometriosis remain unclear.…”
Section: Alterations Of the Cell Cycle In The Granulosa Cellsmentioning
confidence: 99%